Cue integration and context effects in speech: Evidence against speaking rate normalization - Toscano, Joseph C. (2012)
Listeners are able to accurately recognize speech despite variation in acoustic cues across contexts, such as different speaking rates. Previous work has suggested that listeners use rate information (indicated by vowel length; VL) to modify their use of context-dependent acoustic cues, like voice-onset time (VOT), a primary cue to voicing. We present several experiments and simulations that offer an alternative explanation: listeners treat VL as an phonetic cue, rather than as an indicator of speaking rate, and rely on general cue-integration principles to combine information from VOT and VL. We demonstrate that listeners use the two cues independently, that VL is used in both naturally-produced and synthetic speech, and that effects of stimulus naturalness can be explained by a cue-integration model. Together, these results suggest that listeners do not interpret VOT relative to rate information provided by VL and that effects of speaking rate can be explained by more general cue-integration principles.